The Regional And Stratigraphical Context Of Zechstein 3 And 4 Potash Deposits In The British Sector Of The Southern North Sea And Adjoining Land Areas. - Denys B. Smith (Society for Mining, Metallurgy & Exploration, 1978)
Electric logs and cuttings records from Zechstein 3 and 4 strata in boreholes in the British Sector of have been interpreted in the light of numerous cored boreholes through this sequence in north-east England. This interpretation shows that potash salts in the two cycles are thickest and most consistent in a belt 20 to 40 km wide parallel with and a few kilometres from the present basin margin, and are here generally similar in grade to those known onshore. The potash ores in both cycles are mainly of sylvinite in onshore areas, the layered Upper the Southern North Sea Potash of the fourth cycle being rather less variable but generally of appreciably lower average grade than the Boulby Potash of the third cycle. Potash salts in both cycles are highly variable in thickness and grade in basin centre areas where they have been grossly affected by diapirism of the thick second cycle salts.